Expression of S100A12 (EN-RAGE) in cystic fibrosis. Issue 7 (1st July 2003) - Foell, D; Seeliger, S; Vogl, T; Koch, H-G; Maschek, H; Harms, E; Sorg, C; Roth, J
Abstract : Background: Chronic airway inflammation and recurrent infections are a core phenomenon in cystic fibrosis (CF). Diagnosing acute infectious exacerbations is difficult in the presence of chronic inflammatory processes. S100A12 exhibits proinflammatory functions via interaction with the multiligand receptor for advanced glycation end products. Blocking this interaction inhibits inflammatory processes in mice. Methods: The expression of S100A12 in lung specimens of patients with end stage lung disease of CF was investigated, and S100A12 levels in the serum of patients with acute infectious exacerbations of CF were measured. Results: Immunohistochemical studies of CF lung biopsy specimens revealed a significant expression of S100A12 by infiltrating neutrophils. High S100A12 levels were found in the sputum of patients with CF, and serum levels of S100A12 during acute infectious exacerbations were significantly increased compared with healthy controls (median 225 ng/ml v 46 ng/ml). After treatment with intravenous antibiotics the mean S100A12 level decreased significantly. There was also a significant difference between S100A12 levels in patients with acute infectious exacerbations and 18 outpatients without exacerbations (median 225 ng/ml v 105 ng/ml). Conclusions: S100A12 is extensively expressed at local sites of inflammation in CF. It is a serum marker for acute infectious exacerbations. High local expression of S100A12 suggests that this protein has a proinflammatory role during airway inflammation and may serve as a novel target for anti-inflammatory treatments.